2012
DOI: 10.1038/srep00935
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration by polyhedral microcrystals from silkworm virus

Abstract: Bombyx mori cypovirus is a major pathogen which causes significant losses in silkworm cocoon harvests because the virus particles are embedded in micrometer-sized protein crystals called polyhedra and can remain infectious in harsh environmental conditions for years. But the remarkable stability of polyhedra can be applied on slow-release carriers of cytokines for tissue engineering. Here we show the complete healing in critical-sized bone defects by bone morphogenetic protein-2 (BMP-2) encapsulated polyhedra.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…18 We have estimated that 3.6  10 7 BMP-2 polyhedra contain 1 mg of BMP-2 protein. In this study, we mixed either 1.8  10 7 or 3.6  10 6 BMP-2 polyhedra with 200 ml Phosphate Buffered Saline (PBS) and added it dropwise onto a 20 mm  10 mm  2 mm Pelnac Õ atelocollagen sponge (Gunze, Kyoto, Japan), taking care to avoid any runoff of excess liquid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 We have estimated that 3.6  10 7 BMP-2 polyhedra contain 1 mg of BMP-2 protein. In this study, we mixed either 1.8  10 7 or 3.6  10 6 BMP-2 polyhedra with 200 ml Phosphate Buffered Saline (PBS) and added it dropwise onto a 20 mm  10 mm  2 mm Pelnac Õ atelocollagen sponge (Gunze, Kyoto, Japan), taking care to avoid any runoff of excess liquid.…”
Section: Methodsmentioning
confidence: 99%
“…17 In our previous studies, using both in vitro and in vivo rat calvarial bone defect models, polyhedra containing full-length BMP-2 had a similar biological activity to BMP-2 protein and prolonged the period of BMP-2 release to induce new bone more effectively than conventional atelocollagen-BMP-2 protein complexes. 18 Our previous data suggest that therapy with BMP-2 polyhedra improves bone regeneration. However, to date there have been no studies of the usefulness of BMP-2 polyhedra to facilitate the healing of defects in the mandibular alveolar ridge in large animals.…”
Section: Introductionmentioning
confidence: 98%
“…Absorbable collagen sponges or atelocollagen sponges, both of which incorporated polyhedron-encapsulated bone morphogenetic protein-2, have been shown to be effective for the complete and rapid healing of critically sized bone defects in mammals, highlighting the effectiveness of combining polyhedronencapsulated cytokines with biocompatible 3D substitutes to fabricate extracellular matrices that can control in vivo cell activities (26,28,29). However, scaffolds containing mammal-derived components, such as collagen or coagulation factor XIII, may present risks when used in human bodies because they could be contaminated by prions or viruses.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the activity of cytokines encapsulated in polyhedra, which are protein microcrystals of cypovirus, can be stably maintained over long periods in both ex vivo and in vivo environments, and can be slowly released to stimulate the growth and differentiation of many cell types continually (14,(24)(25)(26)(27)(28)(29). Therefore, to determine whether sericin hydrogels can act as scaffolds to support cell growth and differentiation, we cultivated the mouse embryonic stem (ES) cell line EB5 on sericin hydrogels that were overlaid with a medium containing canonical recombinant human leukemia inhibitory factor (rhLIF) or that incorporated polyhedron-encapsulated LIF (24) (SI Appendix, SI Materials and Methods).…”
Section: Expression and Physiological Effects Of Truncated P1a In Silmentioning
confidence: 99%
“…Then, we examined healing in critical-sized bone defects by bone morphogenetic protein-2 (BMP-2) encapsulated polyhedra. ACS impregnated with BMP-2 polyhedra had enough osteogenic activity to promote complete healing in critical-sized bone defects, but ACS with a high dose of rhBMP-2 showed incomplete bone healing, indicating that polyhedral microcrystals containing BMP-2 promise to advance the state of the art of bone healing [136]. …”
Section: Scaffolds For Acellular Bone Tissue Engineeringmentioning
confidence: 99%